1992
DOI: 10.1002/pro.5560011003
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic “interface” peptides alter dimeric assembly of the HIV 1 and 2 proteases

Abstract: Retroviral proteases are obligate homodimers and play an essential role in the viral life cycle. Dissociation of dimers or prevention of their assembly may inactivate these enzymes and prevent viral maturation. A salient structural feature of these enzymes is an extended interface composed of interdigitating N-and C-terminal residues of both monomers, which form a four-stranded 6-sheet. Peptides mimicking one 6-strand (residues 95-99), or two &strands (residues 1-5 plus 95-99 or 95-99 plus 95-99) from the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 24 publications
1
71
0
Order By: Relevance
“…In dihydrofolate reductase (Hall & Frieden, 1989), isoleucyl-t-RNA synthetase (Michaels et al, 1996) and the dimeric retroviral protease (Babe et al, 1992), peptide fragments of the respective proteins specifically inhibited their correct folding and assembly. Because the C-terminal region of RNase H appears to fold late and proper folding of this region is critical for RNase H function, the intermediate we have characterized here represents a potentia1 target for such a folding inhibitor.…”
Section: Implications For the Development Of Inhibitorsmentioning
confidence: 99%
“…In dihydrofolate reductase (Hall & Frieden, 1989), isoleucyl-t-RNA synthetase (Michaels et al, 1996) and the dimeric retroviral protease (Babe et al, 1992), peptide fragments of the respective proteins specifically inhibited their correct folding and assembly. Because the C-terminal region of RNase H appears to fold late and proper folding of this region is critical for RNase H function, the intermediate we have characterized here represents a potentia1 target for such a folding inhibitor.…”
Section: Implications For the Development Of Inhibitorsmentioning
confidence: 99%
“…There is evidence from in vitro transcription-translation assays that the frame shift protein p6* inhibits the processing activity of the HIV protease by blocking the active site in a manner similar to the pepsinogen N-terminal prosegment (James and Sielecki, 1986;Partin et al, 1991 ;Zybarth and Carter, 1995). On the other hand, the C-terminal hexapeptide of p6* was reported to inhibit the protease by preventing its dimerization with even larger affinity than the respective C-terminal peptide of the protease itself, which to-gether with the N-termini forms a four-stranded antiparallel psheet (BabC et al, 1992;Schramm et al, 1993;Weber, 1990).…”
mentioning
confidence: 99%
“…Because dimerization is required to generate a functional enzyme, it has been suggested that agents that can bind at the dimer interface and prevent subunit association could represent a novel therapeutic approach tb stem the progression of AIDS (Restle et al, 1990;Babe et al, 1992;Nanni et al, 1993). Very recently, several peptides derived from the connection domain have been shown to inhibit the dimerization of RT (Divita et al, 1994).…”
mentioning
confidence: 99%